eHealth tools for childhood cancer survivorship care: A qualitative analysis of survivors', parents', and general practitioners' views - Maria Schaffer; Jordana K. McLoone; Claire E. Wakefield; Mary-Ellen Brierley; Afaf Girgis; Maria C. McCarthy; Elysia Thornton-Benko; Raymond J. Chan; Karen A. Johnston; Richard J. Cohn; Christina Signorelli (Elsevier, 2022)
Objective: We assessed the acceptability of, and perceived benefits/barriers to, using Electronic health (eHealth) technology for childhood cancer survivorship care. Methods: We interviewed survivors, their parents, and their nominated GP. We described a hypothetical eHealth tool to manage survivorship care and asked their likely use of, and perceived benefits/concerns for, the use of the tool. Results: 31 survivors (mean age = 27.0), 29 parents (survivors' mean age = 12.6), and 51 GPs (mean years practising = 28.2) participated. Most survivors/parents (85%) and GPs (75%) indicated that they would be willing to use an eHealth tool. Survivors/parents reported that an eHealth tool would increase their confidence in their ability, and their GP's ability, to manage their survivorship care. GPs agreed that an eHealth tool would provide easier access to survivors' medical information and increase their capacity to provide support during survivorship. Some GPs (7%) and survivors (43%) reported being hesitant to use eHealth tools due to privacy/security concerns. Conclusion: Overall, eHealth tools appear acceptable and may help to improve the management of late effects for childhood cancer survivors and assist their GPs to coordinate their care. Innovation: Concerns raised by key stakeholders should be addressed in the design of eHealth technologies to optimise their uptake and effectiveness.